KEEFEKTIFAN MODEL PEMBELAJARAN DEEP LEARNING DALAM KURIKULUM MERDEKA TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMP - Mukmina Mukmina; Dwi Ivayana Sari (Jurnal Manajemen Pendidikan, 2026)
Education is a basic right that every individual must obtain from an early age because it plays a vital role in developing their potential. Through education, a person can improve their abilities, knowledge, skills, and quality of life. This study aims to determine the effect of implementing the Deep Learning learning model on student learning outcomes in the Independent Curriculum. The research method used is a quantitative approach with a quasi-experimental research design, Posttest Non-Equivalent Control Group Design. The research sample consisted of 60 students, consisting of 30 students in the control class and 30 students in the experimental class, namely students of grades VIII-B and VIII-D of SMP Negeri 1 Kokop. The research instruments used included observation sheets, student response questionnaires, and posttest questions. Data analysis was carried out through normality tests using Shapiro-Wilk, homogeneity tests using Levene, and hypothesis testing using the Independent Samples t-test. The results showed that there were significant differences in learning outcomes between students who participated in Deep Learning learning and students who participated in conventional learning. The significance value obtained was 0.034 (p < 0.05), indicating that the Deep Learning model had a positive effect on improving student learning outcomes. Thus, the Deep Learning model is effectively implemented in learning to improve student learning outcomes.